(3cJGH aj Yde GdRQObIs - (3YHO Gddg Hf GdHOQ GdHjWGQ GdeUQj, GHf GdefPQ, CHh HcQ , J (B741 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd (B((3GdabjQ(B) (3Edi Gddg JYGdi gPG cJGH aj Yde GdRQObI LeYJg eeG LQHJg , hGdPi LQH HMVhQi , heeG LQH hVM ef bhd GdCSJGPjf s
(3BNQgG (B:s
(3hbO RYe bhe ef GdadGSaI Gf GdaQS GdeUQi EPG JYOi SHY Sfjf hde jfab aEfg jHdZ CQHYjf SfI, hGddg SHMGfg hJYGdi GYde s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B70 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B76s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B205 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B282 s
Keywords: (3GdWHs